Hybrid composites of conductive polyaniline and nanocrystalline titanium oxide prepared via self-assembling and graft polymerization - Li, Jing; Zhu, Lihua; Wu, Yinghui; Harima, Yutaka; Zhang, Aiqing; Tang, Heqing (Polymer (Guilford), 2006)
After TiO 2 nanoparticles were surface modified, conductive polyaniline (PANI) layer was chemically grafted on the surface of the self-assembled monolayer (SAM) coated TiO 2 nanoparticles, resulting in PANI/SAM-TiO 2 composites. In the preparation process of the hybrid composites, γ-aminopropyltriethoxysilane was used as a coupling agent to form a dense aminopropylsilane monolayer with active sites for the graft polymerization of aniline. The resulted composite nanoparticles were characterized by using TEM, FTIR, TGA, and UV–vis-diffuse reflectance spectroscopy. The thermogravimetric analysis confirmed that the inserted SAM layer improved the thermal stability of the PANI–TiO 2 nanocomposites. Compared with neat-TiO 2 nanoparticles without any surface modification, moreover, the PANI/SAM-TiO 2 nanocomposites showed better photocatalytic activity in photodegradation of methyl orange under sunlight, which was partly attributed to the sensitizing effect of PANI.